Short sleep duration is associated with shorter telomere length in healthy men: findings from the Whitehall II cohort study. - Marta Jackowska; Mark Hamer; Livia A Carvalho; Jorge D Erusalimsky; Lee Butcher; Andrew Steptoe (PLoS ONE, 2012)
Shorter telomere length and poor sleep are more prevalent at older ages, but their relationship is uncertain. This study explored associations between sleep duration and telomere length in a sample of healthy middle and early old age people.Participants were 434 men and women aged 63.3 years on average drawn from the Whitehall II cohort study. Sleep duration was measured by self-report.There was a linear association between sleep duration and leukocyte telomere length in men but not in women (P = 0.035). Men reporting shorter sleep duration had shorter telomeres, independently of age, body mass index, smoking, educational attainment, current employment, cynical hostility scores and depressive symptoms. Telomeres were on average 6% shorter in men sleeping 5 hours or fewer compared with those sleeping more than 7 hours per night.This study adds to the growing literature relating sleep duration with biomarkers of aging, and suggests that shortening of telomeres might reflect mechanisms through which short sleep contributes to pathological conditions in older men.